First Data on Gastrointestinal Parasitic Infection in the Red-Legged Partridge (Alectoris rufa) in Italy - Loredana Polello; Anna Rita Molinar Min; Angela Fanelli; Ennio Negri; Andrea Peano; Pier Giuseppe Meneguz; Paolo Tizzani (Diversity, 2021)
The Red-legged partridge (Alectoris rufa) is a Mediterranean Galliformes, recently classified as Near Threatened by the International Union for the Conservation of Nature, due to the constant and significant decline of its global population. While the gastrointestinal parasites of the species are well studied in some part of its range (Iberian peninsula), limited information is available for the Italian populations, that represent the eastern limit of the species range. This study was conducted to fill this gap of knowledge, determining the composition, richness, prevalence, intensity and abundance of A. rufa gastrointestinal parasite community in two populations in Italy. During the autumn seasons 2008–2009 and 2009–2010, necropsies were conducted on 18 Red-legged partridge from the southern part of Alessandria province (Piedmont, northwestern Italy) and 34 from the Parma province (Emilia Romagna, northern Italy). All the animals were examined for the presence of gastrointestinal parasites. Additionally, 229 fecal samples were collected from live animals in Alessandria province. Prevalence, abundance and intensity of infection were calculated for each parasite species, except for coccidia for which only the prevalence was determined. The following parasites were observed: Heterakis gallinarum, Ascaridia spp., Ascaridia columbae, Raillietina spp., Eimeria spp. The highest parasite prevalence was found in Alessandria province for Eimeria sp., infecting almost half of the sampled animals (P: 45%, CI95%: 39–51). Eimeria sp. was also the most prevalent parasite in Parma province but with much lower prevalence (P: 19%, CI95%: 5–32). Intestinal helminths prevalence ranged from 3% (CI95%: 0–9) for A. columbae and Raillietina spp. (Parma Province) to 9% for H. gallinarum in both Parma (CI95%: 0–19), and Alessandria province (CI95%: 0–22). To our knowledge, this is the first study providing information on the gastrointestinal parasites of the Red-legged partridge in Italy. Ascaridia columbae, a parasite typical of the domestic pigeon, was reported for the first time in A. rufa. The epidemiological descriptors reported herein could serve as a basis for future studies, allowing for epidemiological comparison across countries, locations, and time periods.